2022
DOI: 10.1152/ajpcell.00162.2021
|View full text |Cite
|
Sign up to set email alerts
|

The role of L-type amino acid transporter 1 (Slc7a5) during in vitro myogenesis

Abstract: Satellite cells are required for muscle regeneration, remodeling, and repair through their activation, proliferation, and differentiation; however, how dietary factors regulate this process remains poorly understood. The L-Type amino acid transporter 1 (LAT1) transports amino acids, such as leucine, into mature myofibers, which then stimulates protein synthesis and anabolic signaling. However, whether LAT1 is expressed on myoblasts and is involved in regulating myogenesis is unknown. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This example of LAT1 dispensability has been shown in gastrocnemius of LAT1-knockout mice that exhibit increased LAT2 mRNA expression ( Slc7a8 ) and do not display altered intra-gastrocnemius leucine content following a fed state (and display elevated leucine content under a fasting state) [ 55 ]. Our findings seem to agree with other experiments showing LAT1 abundance is not dependent on cell culture media leucine content in myocytes [ 56 ], nor dependent on dietary protein within skeletal muscle [ 57 ]. Together, our study provides a first level of evidence suggesting PPAR β / δ agonism with GW may upregulate BCAA metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…This example of LAT1 dispensability has been shown in gastrocnemius of LAT1-knockout mice that exhibit increased LAT2 mRNA expression ( Slc7a8 ) and do not display altered intra-gastrocnemius leucine content following a fed state (and display elevated leucine content under a fasting state) [ 55 ]. Our findings seem to agree with other experiments showing LAT1 abundance is not dependent on cell culture media leucine content in myocytes [ 56 ], nor dependent on dietary protein within skeletal muscle [ 57 ]. Together, our study provides a first level of evidence suggesting PPAR β / δ agonism with GW may upregulate BCAA metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…At present, it is believed that the regulation mechanism of cell fusion is mainly related to the adhesion molecules and membrane protein structures on the cell membrane, such as P4-ATPase flippase subunit CDC50A and L-type amino acid transporter 1 (LAT1). [39][40][41] As one of the characteristics of skeletal myogenic differentiation, the fusion of individual myocytes into multinucleated mature myotubes has also been shown to be regulated by genetic mechanisms distinct from myogenic differentiation. Some studies have found that small open reading frames (sORF) exist in lncRNA, and the sORF-encoded micropeptide may be related to cell fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we elected to focus the current study on the expression of LAT1, which transports large amino acids including leucine, isoleucine, valine, phenylalanine, methionine, tyrosine, histidine, and tryptophan into the cell, and its relationships with body weight, tumor cell proliferation, and immune infiltration. Prior literature indicates that LAT1 is involved in protein synthesis [ 40 , 41 ] and mTORC1 activity [ 42 , 43 ], and may also modulate the anti-tumor immune response [ 44 47 ]. Overexpression of LAT1 has been observed in a plethora of tumor types ranging from lung to endometrial to liver, but fewer studies of the relationship between LAT1 and breast cancer exist [ 48 ].…”
Section: Discussionmentioning
confidence: 99%